Effect of pregnancy on the auditory and visual reaction time - Mehta, Rupali; Kurmi, Naren; Kaur, Manjinder; Verma, Anjana (International Journal of Research in Medical Sciences, 2017)
Background: The auditory and visual pathways are complex multi-synaptic neuronal circuits prone to alteration in conductivity under the influence of various neuro-hormonal modulators. The female sex steroids have shown significant effect on these circuits during different phases on menstrual cycle and pregnancy. Methods: The present study was designed with an aim to find out the auditory and visual reaction time variations during different trimesters of pregnancy. The healthy non pregnant women, in premenstrual phase were grouped as controls (Group NP; n=30) whereas the cases were further divided into 3 groups depending on the duration of pregnancy as Groups T1,T2and T3 with 30 volunteers in each. Results: The ART and VRT were measured using RTM-608 (Medicaid) in the Obstetrics and Gynaecology department of our hospital. The observations were recorded and analysed using one way ANOVA and post hoc Tukey test. A significant increase (p<0.001) in reaction time of both the auditory and visual pathways has been observed in Group T1 as compared to Group non-pregnant. Whereas Group T2 and T3 had shown not much difference of ART and non-significant increase of VRT when compared to Group NP. The increased reaction time could be attributed to the raised HCG levels during 1st trimester, modulating the neuronal conductivity during that period. Conclusions: However, the non-significantly increased or similar reaction time in Group T2and T3could be attributed to increased levels of estrogen and progesterone. Hence, these hormones have neuromodulatory effect on the neuronal excitability, plasticity and excitability, though the direct effect of HCG needs further exploration.